2018
DOI: 10.1111/eff.12450
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, discharge and development shape the larval diets of threatened green sturgeon in a highly managed section of the Sacramento River

Abstract: Feeding at early fish life stages is a key determinant of survival to recruitment. To understand the environmental and developmental determinants of early life stage feeding in ESA-threatened green sturgeon (Acipenser medirostris), we performed a diet study in a highly managed section of California's Sacramento River, where temperature and discharge are controlled by dam releases. Utilising field collections from 2012 to 2016, we assessed the impacts of temperature, discharge and morphological development on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…By introducing larval green sturgeon condition to a winter‐run egg survival model in multi‐object optimization, we identify a Pareto frontier with a corner that is optimal for both species. Our study corroborates others which found that indices of health in larval green sturgeon are enhanced at higher temperatures (Hamda et al, ; Mayfield & Cech, ; Poletto et al, ; Zarri & Palkovacs, ), but body condition appears to be more sensitive to changes in discharge at the range of environmental variables experienced in our study region (Figure a). Furthermore, the positive correlation of green sturgeon body condition with temperature may be moderated by food availability, as fish exposed to warm temperatures with low food availability show very low body condition (Poletto et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By introducing larval green sturgeon condition to a winter‐run egg survival model in multi‐object optimization, we identify a Pareto frontier with a corner that is optimal for both species. Our study corroborates others which found that indices of health in larval green sturgeon are enhanced at higher temperatures (Hamda et al, ; Mayfield & Cech, ; Poletto et al, ; Zarri & Palkovacs, ), but body condition appears to be more sensitive to changes in discharge at the range of environmental variables experienced in our study region (Figure a). Furthermore, the positive correlation of green sturgeon body condition with temperature may be moderated by food availability, as fish exposed to warm temperatures with low food availability show very low body condition (Poletto et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…These two objectives are of primary importance for Shasta Dam releases but likely harm ESA‐threatened green sturgeon, which depend on warm low flow conditions to support larval growth. High discharge has a strong impact on developing green sturgeon larvae swimming ability and is associated with decreased prey richness and diet count (Verhille et al, ; Zarri & Palkovacs, ). By introducing larval green sturgeon condition to a winter‐run egg survival model in multi‐object optimization, we identify a Pareto frontier with a corner that is optimal for both species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, conditions encountered by offspring during incubation, and maternal effects are important to growth and survival [ 98 ]. The period where larvae shift from endogenous reserves to exogenous feeding is particularly critical for survival [ 13 , 99 ], due to the risk of predation and starvation at these early life stages [ 100 ]. Both sources of mortality have been tied to body size.…”
Section: Discussionmentioning
confidence: 99%
“…nauplii feed on the growth and survival of larval... mechanism of ingesting feed in sturgeons depends on the species. The mouths of predatory sturgeons open to the front, while those of benthic feeding sturgeons are directed downward (Zarri and Palkovacs 2019). However, this type of feeding limits maximum prey size and is not effective for catching large or highly mobile prey (Miller 2004).…”
Section: Prey Sizementioning
confidence: 99%